Comparative Morphological Assessment of Swamp Buffalo (Bubalus bubalis) Populations in East Java, Indonesia: A Case Study of Tuban and Pacitan Districts - Abdul Basith; Laily Isnaini Rahmawati (Politeknik Pembangunan Pertanian Manokwari, 2026)
The swamp buffalo (Bubalus bubalis) is a critical domestic ruminant in Indonesia. Continuous morphological evaluation is vital for conserving this genetic resource. This study characterized qualitative and quantitative traits of swamp buffalo populations in Tuban and Pacitan districts, East Java, Indonesia. Using purposive sampling, 64 adult buffaloes (32 per district) were assessed. Buffalo samples aged more than 25 months, regardless of sex. Qualitative analysis identified regional variation in body stature and coloration between populations. Quantitative metrics included chest girth, body length, height, head length, neck length, tail length, horn length, and estimated body weight. Tuban buffaloes exhibited a chest girth of 182.31 ± 24.76 cm, body length of 148.94 ± 22.34 cm, height of 119.56 ± 12.48 cm, head length of 46.63 ± 7.80 cm, neck length of 42.88 ± 7.70 cm, tail length of 76.63 ± 9.15 cm, horn length of 14.44 ± 3.98 cm, and estimated body weight of 1045.49 ± 401.51 kg. Pacitan buffaloes displayed higher averages, including a chest girth of 194.44 ± 24.49 cm, body length of 152.25 ± 23.83 cm, height of 122.13 ± 16.81 cm, head length of 49.88 ± 5.28 cm, neck length of 44.31 ± 8.24 cm, tail length of 77.69 ± 10.24 cm, horn length of 13.63 ± 3.90 cm, and estimated body weight of 1208.98 ± 415.66 kg. Despite these differences, one-way ANOVA revealed no statistically significant divergence (p > 0.05) in quantitative traits between populations. These findings provide critical baseline data for conserving East Java’s swamp buffaloes.